ECOPRENEURSHIP EDUCATION BERBASIS PRAKARYA DALAM KURIKULUM 2013 - Anih, Euis (STKIP Subang, 2015)
In 2020-2030 an estimated 70 % of Indonesia's population of productive age. This is an opportunity that needs to be optimized through education so that it appears ecopreneurship new entrepreneurs who care about the environment in anticipation of not match jobs with people who need a job (as an employee). This paper describes the concept ecopreneurship education, the urgency of ecopreneurship education, and implementation craft-based ecopreneurship education in the curriculum of 2013. Based on the results of the study are known to still craft curriculum subjects that need to be improved because there is less and less environmentally friendly in accordance with ecopreneurship. Ecopreneurship education is the use of content-based craft subjects as substance entrepreneurship education (intra and extracurriculum) combined with the concept of environmental awareness in entrepreneurship that will produce eco-friendly crafts, eco-innovation, eco- resources, and eco- commitment.